Anxiety, perceived control and pandemic behaviour in Thailand during COVID-19: Results from a national survey. (March 2021) - Goodwin, Robin; Wiwattanapantuwong, Juthatip; Tuicomepee, Arunya; Suttiwan, Panrapee; Watakakosol, Rewadee; Ben-Ezra, Menachem
Abstract: Anxiety, perceived control and trust in information sources have all been shown to significantly influence health and social behaviours during pandemics. We measured these factors in a nationally representative on-street survey collected across five regions of Thailand (N = 1000, May 2020, response rate 82.6%). Anxiety was positively associated with stocking up on food (OR 2.62 (95% CI 1.88–3.66)) and taking vitamins (OR 2.37 (1.59–3.54)); perceived control with (recommended) coughing into an elbow (OR 2.42 (1.80–3.26)), checking on others (OR 1.52 (1.00–2.31)), and negatively with stockpiling (OR 0.72 (0.55-0.96)). Those relying on family/friends, doctors online or foreign sources were more likely to take vitamins (ORs 4.11, 2.88. 2.82), respondents using TV news less likely to stock up on food (OR 0.57 (0.37-0.86)) and to wear a mask for self-protection (OR 0.27 (0.10-0.73)). Comparing findings with analogous cross-sectional data on anxiety collected at the start of the pandemic (Feb 2020, Goodwin et al., 2020) there was no significant difference between personal anxiety in the two surveys (F (1, 1197) = 0.72, p = .40)) but perceived control was lower in the later survey (F (1, 1197) = 6.72 p = .01)). Findings suggest reduced perceived control as the pandemic developed and illuminate possible negative impacts of anxiety and low sense of control on pandemic behaviours.